1.全完按定理:
P(A ̄B ̄C)=P(C)-P(A ̄B ̄) ̄
P(A ̄B ̄) ̄=1-P(A ̄B)-P(AB ̄)-P(AB)
P(A ̄B)=P(B)-P(AB)
P(AB ̄)=P(A)-P(AB)
A ̄B ̄∪C=P(A ̄B ̄)+P(C)-P(A ̄B ̄C)
自己代入数据计算吧
2.A、B互不相容,所以A属于B ̄,故AB ̄=A,所以P(AB ̄)=P(A)
3.P(AB ̄)=P(A)-P(AB)
(13/15)*(12/14)*(11/13) X=0
P(X)= (2/15)*(13/14)*(12/13)+(13/15)*(2/14)*(12/13)+(13/15)*(12/14)*
(2/13) X=1
(13/15)*(2/14)*(1/13)+(2/15)*(13/14)*(1/13)+(2/15)*(1/14)*1 X=2
由于@=5/9(T-32),故T=(9@+160)/5
由于T~N(98.2,2),所以(T-98.2)/根号2~N(0,1),将T用@代入,得
(9/5@+32-98.2)/根号2=(9/5@-66.2)/根号2=9/5(@-331/9)/根号2=(@-331/9)/根号(50/81)~N(0,1),所以@~N(331/9,50/81)